2020
DOI: 10.1055/s-0039-3402007
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of the Cerebral Palsies: Contribution of Population-Based Neuroimaging Data

Abstract: Background Surveillance of cerebral palsy in Europe (SCPE) presents the first population-based results on neuroimaging findings in children with cerebral palsy (CP) using a magnetic resonance imaging classification system (MRICS). Method MRIs of children with CP born between 1999 and 2009 from 18 European countries were analyzed. MRICS identifies patterns of brain pathology according to timing during brain development which was analyzed with respect to CP subtypes and gestational age. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
38
3
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 19 publications
6
38
3
1
Order By: Relevance
“…Using the SCPE database, Horber and coll. recently published that more than 80% of the children born <32 weeks GA had predominant white matter injury ( 28 ). Children born <32 weeks had fewer maldevelopments, a lesser proportion of gray matter injuries and consequently a greater proportion of predominant white matter injuries than children born MPT (32–36 weeks).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the SCPE database, Horber and coll. recently published that more than 80% of the children born <32 weeks GA had predominant white matter injury ( 28 ). Children born <32 weeks had fewer maldevelopments, a lesser proportion of gray matter injuries and consequently a greater proportion of predominant white matter injuries than children born MPT (32–36 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…A very first analysis using the MRI Classification System (MRICS) developed and validated by the Surveillance of Cerebral Palsy in Europe (SCPE) collaboration ( 27 ) showed a very clear lesional pattern in children born VPT with 80% having predominant white matter lesions (such as periventricular leucomalacia or sequelae of hemorrhage). Data also suggested that this proportion increases with decreasing GA at birth ( 28 ).…”
Section: Introductionmentioning
confidence: 95%
“…The structure-function relationship with regard to neuroimaging findings and CP has previously been addressed by the SCPE in the Reference and Training Manual 1 (14) and in a previous study (13), where the distribution of MRI patterns was reported by different gestational ages and CP subtypes.…”
Section: Introductionmentioning
confidence: 97%
“…One is the MRI classification system (MRICS), developed by the Surveillance of Cerebral Palsy in Europe, SCPE (11,12). A first report of European population-based results of the MRICS was recently published (13). The quality of the MRICS data relies on training of the register partners, who, guided by the Reference and Training Manual and annual exchange and discussions, do the classification of MRI reports and scans and are instructed to classify the neuroimaging pattern which most likely is the cause of the CP.…”
Section: Introductionmentioning
confidence: 99%
“…6 In this issue, the first analysis of magnetic resonance imaging (MRI) in the European CP database confirms on a large population basis, that CP is mainly due to lesions which are considered acquired during second or third trimester of pregnancy or around birth, and that maldevelopments are arising during embryonic and early foetal life are relatively uncommon. 7 In preterm-born children, lesions typical for their gestational age at birth were by far predominant. This is especially interesting with respect to the epidemiological evidence of a decrease in CP morbidity.…”
mentioning
confidence: 99%